Penguatan Pengelolaan Sampah Berbasis Bank Sampah melalui Edukasi dan Pendampingan Masyarakat di Kelurahan Andalas, Kota Padang - Syaifuddin Islami; Hadi Rafindo; Dewi Anggraini; Desi Eka Putri; Hardinalis Kobal; Budiyanti Budiyanti; Yudas Sabaggalet; Fanny Wulanda (Universitas Negeri Gorontalo, 2026)
Urban waste management remains a major challenge, particularly in densely populated residential areas where waste generation continues to increase while source-based waste management practices remain limited. This community service program aimed to strengthen community capacity in waste management through waste bank-based education at the Andalas Sepakat Waste Bank Unit, RT 02/RW 04, Andalas Subdistrict, Padang Timur District, Padang City. The program employed a community participatory approach involving education, technical assistance, and the introduction of appropriate technologies. The activities included waste savings schemes, household-scale organic waste treatment using solar biodigesters, organic waste bioconversion with Black Soldier Fly (BSF) maggots, and the production of eco enzyme from household organic waste. The implementation demonstrated that waste bank activities can be integrated with appropriate technologies to support household waste management while expanding the educational role of the waste bank within the community. Program evaluation also identified that member participation remains a challenge for sustaining community-based waste management initiatives. These activities indicate that integrating environmental education, community participation, and appropriate technologies provides a practical approach to strengthening sustainable waste management at the neighborhood level.